FAMOUS SPORTS COMPETITIONS IN BRITAIN - Ikromov Jaloladdin; Botirova Hakima (Лучшие интеллектуальные исследования, 2023)
Annotation: Sports competitions in Britain have a long and storied history, encompassing a wide range of athletic disciplines and drawing enthusiastic audiences from around the world. This abstract provides a brief overview of some of the most renowned and influential sports competitions held in Britain, highlighting their cultural significance and global impact.